(untitled) (AmS-Skrifter, 2020)
The Hanse played not only a prominent economical role in the North Atlantic but the Germans also consistently influenced the culture of the people with whom they interacted and traded. Their presence led to a sort of cultural colonialism in Northern Europe, which, among others things, substantially shaped the Scandinavian languages. For several reasons, the Icelandic language was not influenced in the same way as the other Scandinavian languages; yet, one can find some traces of German in administrative language dating back to the Middle Ages. Furthermore, ‘cultural colonization’ by the Germans also certainly took place through the Reformation in Iceland. It was the German merchants who took the first seeds of the new faith with them to Iceland and marked their ‘conquest’ by building a Lutheran church. In this way, the merchants – like colonialists – claimed a space on foreign ground for themselves, where language played a very central role.